Halorarius litoreus gen. nov., sp. nov., Halorarius halobius sp. nov., Haloglomus halophilum sp. nov., Haloglomus salinum sp. nov., and Natronomonas marina sp. nov., extremely halophilic archaea isolated from tidal flat and marine solar salt - Sun, Ya-Ping; Wang, Bei-Bei; Wu, Zhang-Ping; Zheng, Xi-Wen; Hou, Jing; Cui, Heng-Lin (Frontiers in Marine Science, 2023)
Five novel halophilic archaeal strains, named BND22T, ZY10T, ZY41T, ZY58T, and ZY43T, were isolated from the coastal saline sediment of the intertidal zone located in Qingdao and the natural sea salt produced from Huanghua marine solar saltern, PRChina. These five strains demonstrated the typical morphology and growth characteristics of haloarchaea. The comparison of 16S rRNA gene revealed that strain BDN22T was associated with Salinirubellus salinus ZS-35-S2T (95.2% similarity), strain ZY10T was related to Halosegnis rubeus F17-44T (95.1% similarity), both strains ZY41T and ZY58T were closely related to Haloglomus irregulare F16-60T (98.1% and 98.2% similarities, respectively), and strain ZY43T was close to Natronomonas salina YPL13T (98.0% similarity). In addition to the 16S rRNA gene, the rpoB′ gene is undoubtedly another important molecular marker for the identification of halophilic archaea, and concatenated-conserved-protein phylogeny was widely used in archaeal classification in recent years. Phylogenetic and phylogenomic analyses based on rpoB′ genes and 122 concatenated archaeal protein genes showed that these haloarchaea construct three different clades and gathered together with the current members of Haloarculaceae. Strains BND22T and ZY10T formed two distinct clades separated from Salinirubellus salinus ZS-35-S2T and Halosegnis members, strains ZY41T and ZY58T clustered with Haloglomus irregulare F16-60T, and strain ZY43T gathered with the current members of Natronomonas. The ANI, DDH, and AAI values of these five strains against phylogenetic neighbours were no more than 91%, 45%, and 92%, respectively, far below the cut-off values for species delineation, supporting their placements in new taxa. Based on the phenotypic, chemotaxonomic, phylogenetic, and phylogenomic properties, these five strains represent five novel taxa of the family Haloarculaceae, Halorarius litoreus gen. nov., sp. nov. (type strain BND22T = CGMCC 1.18780T = JCM 34966T), Halorarius halobius sp. nov. (type strain ZY10T = CGMCC 1.17475T = JCM 34319T), Haloglomus halophilum sp. nov. (type strain ZY41T = CGMCC 1.17030T = JCM 34161T), Haloglomus salinum sp. nov. (type strain ZY58T = CGMCC 1.17216T = JCM 34163T), and Natronomonas marina sp. nov. (type strain ZY43T = CGMCC 1.17202T = JCM 34162T). This is the first report of description of a novel haloarchaeon isolated from a marine intertidal zone.